so I have to prove this using the binomial theorem: $$\sum_{k=0}^n{(-1)^k\begin{pmatrix}n\\k\end{pmatrix}}=0$$

I know the binomial theorem states: $(x+y)^n=\sum_{k=0}^n{\begin{pmatrix}n\\k\end{pmatrix}x^{n-k}\cdot y^k}$.

I can also see that the $(-1)^k$ will be alternating so I will get $+1-1+1-1...$. However, I'm not sure how to show it will $=0$. Thanks.


You can use the "twist" of your binomial theorem $$(x-y)^n=\sum_{k=0}^n (-1)^k\binom{n}{k}x^{n-k}y^k.$$

  • $\begingroup$ This will prove that it will = 0? $\endgroup$ – KFC Sep 25 '15 at 11:54
  • $\begingroup$ @KFC you only need to let $x=y=1$. $\endgroup$ – Asydot Sep 25 '15 at 12:02

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.